A Review on Power Generation System - Aaqib Mukhtar Wani; Jai Singh Arya, (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2022)
Electricity is major requirement for daily life activities. Without electricity the domestic and industrial operation cannot be performed. But there exists several issues during these processes. However lot of research have been made to solve issues but still there are some problems such as Lack of clean & reliable energy sources, Intraday load & need, no access to electricity, Pollution from thermal power plants, Poor pipeline connectivity & infrastructure, Inadequate last mile connectivity, Average transmission, distribution & consumer-level losses etc. In previous research SOLAR PV –WIND Hybrid power generation system approach has been used. As it is known that Renewable energy sources such as energy generated from solar, biomass, wind, geothermal, hydro power, and ocean resources have been considered as a technological option. It could help in generating clean energy. But there are certain limitations of tradition work such as solar energy is not available 24 hours. Even in winter the solar production is negligible.